2021
DOI: 10.1088/1361-6641/ac2ddf
|View full text |Cite
|
Sign up to set email alerts
|

An efficient low-temperature triethylamine gas sensor based on 2D ultrathin SnO2 nanofilms

Abstract: The quest to develop inexpensive chemical sensing materials that are energy-efficient, portable, and with efficient performance lies at the center of next-generation sensor development. Owing to their low cost, easy preparation, high response, and smooth integration with electronic circuits, metal oxide semiconductors have received particular attention. Yet, metal oxide semiconductor based sensors often suffer from high power consumption due to their high operating temperature, which hinders them from practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The test results show that the high response to 50 ppm TEA can reach 43.771 at 268 • C. Meanwhile, the low detection limit (1 ppm) and rapid response/recovery are also advantages of the material. In one recent report, Liu et al [69] designed 2D ultrathin SnO 2 nanofilms for manufacturing low-temperature TEA gas sensors. They studied the effect of calcination temperature on crystal crystallization and found that with the increase in temperature, the crystal size decreased, and the uniformity and density of the surface particles gradually increases.…”
Section: Two-dimensional (2d) Nanomaterialsmentioning
confidence: 99%
“…The test results show that the high response to 50 ppm TEA can reach 43.771 at 268 • C. Meanwhile, the low detection limit (1 ppm) and rapid response/recovery are also advantages of the material. In one recent report, Liu et al [69] designed 2D ultrathin SnO 2 nanofilms for manufacturing low-temperature TEA gas sensors. They studied the effect of calcination temperature on crystal crystallization and found that with the increase in temperature, the crystal size decreased, and the uniformity and density of the surface particles gradually increases.…”
Section: Two-dimensional (2d) Nanomaterialsmentioning
confidence: 99%
“…9,10 Metal oxide semiconductor (MOS) gas sensor has a wide range of application prospects due to its high response value, low price, and simple fabrication process. The MOS materials including ZnO, 5 WO 3 , 11 SnO 2 , 12 In 2 O 3 , 13 MoO 3 , 14 Fe 3 O 4 , 15 Co 3 O 4 , 16 NiO 17 have been widely reported to detect TEA.…”
Section: Introductionmentioning
confidence: 99%
“…The gas sensor mainly has an electrochemical gas sensor, a solid electrolyte gas sensor, a semiconductor gas sensor, and others. , Metal oxide semiconductor (MOS) gas sensor has a wide range of application prospects due to its high response value, low price, and simple fabrication process. The MOS materials including ZnO, WO 3 , SnO 2 , In 2 O 3 , MoO 3 , Fe 3 O 4 , Co 3 O 4 , NiO have been widely reported to detect TEA.…”
Section: Introductionmentioning
confidence: 99%